Electrical properties of solution-derived KNaNbO3-based ferroelectric ceramics thin film - Pang, Thomas Junyong. (2009)
Very recently, due to miniaturization of devices and rising environmental concern over the usage of lead, lead-free based thin films have attracted immerse amount of attention world-wide. Potassium sodium niobate (KNN) have been selected as the more promising lead-free based ferroelectric material. However, the leakage current problem degrades its electrical properties and affects its performance. In this work, WO3 and additive polymer were added into K0.55Na0.55NbO3 and their effects on dielectric, ferroelectric, and piezoelectric properties are studied. WO3 doping level of 0.1 mol % has the optimal effect of suppressing oxygen vacancies, and maintaining charge neutrality of KNN system. It gives stable K of 685 and low D of 0.048 over a range of frequency (102 Hz - 106 Hz). xWO3–doped KNN thin films (x=0.2, 1 and 2 mol% WO3) exhibit unstable dielectric constant and loss with frequency. WO3 doping did not show significant improvement in the ferroelectric and piezoelectric property of KNN films. Poor asymmetrical P-E hysteresis loops with low remnant polarizations are obtained. WO3 doping level higher than 0.5 mol % results in the rounding of P-E hysteresis loop and a decrease in d33. Heat treatment was found to be effective in improving K and d33. The degradation in electrical property of xWO3–doped KNN films (x=0.2, 1 and 2 mol% WO3) was found to be closely related to the unusual rectangular strips phenomenon formed on the surface of the KNN films. Polymer modified KNN films show optimal K and D for molecular weight (Mw) of 300 and Mw higher than 300 degrades dielectric and ferroelectric property of KNN films. Also, the heat treatment with polymer-modified KNN was found to degrade dielectric property. Polymer-modified KNN film exhibit poor asymmetrical P-E hysteresis loops with low remnant polarizations as compared to film without modification.